Uma sequência didática para o ensino da radioatividade no nível médio, com enfoque na história e filosofia da ciência e no movimento CTS - Resquetti, Silvia Oliveira (2013)
The insertion of Modern and Contemporary Physics in the curriculum of High school is a topic that has been widely discussed by researchers in Physics teaching since the late 1970s, however there is evidence that updating the curriculum with the insertion of Modern and Contemporary Physics still does not meet expectations. Researches (BROCKINGTON; PIETROCOLA, 2005; OLIVEIRA, VIANNA; GERBASSI, 2007; SIQUEIRA; PIETROCOLA, 2007) indicate that there are few studies that present proposals for the teaching of these topics. Thus, we decided to develop a methodological proposal for the teaching of radioactivity in High school, focusing on the relationship between Science, Technology and Society (STS) and History and Philosophy of Science (HPS). For the construction of the proposal, we investigated how the theme radioactivity is presented in textbooks of physics of PNLD/2012. In addition to the textbooks, we applied a questionnaire to ten physics teachers of public schools of Paraná, aiming to get informative data about what they think and experience on the subject. We chose the Analysis of Content, of Bardin (1977), to analyze textbooks and the teachers' answers. Based on the results obtained in the investigation, we developed a didactic sequence to the teaching of radioactivity in High School. The primary methodological proposal was presented to the teachers and, during the meeting, the group was asked to evaluate the activities and accomplish educational interventions. From the suggestions of the teachers, the didactic sequence was reconstructed to meet the expectations of the teachers involved.